(untitled) (Editora Impacto Científico, 2025)
This work presents a specification of a proposal to use WiMAX technology for the design of the Digital Inclusion Centers of Fortaleza (CIDFs), due to its lower cost and ease of installation. The CIDFs represent a high level of educational and social outreach for the community, as they will be installed near municipal schools in Fortaleza. The CIDFs project aims to install rooms equipped with state-of-the-art computers with broadband internet access near municipal schools in Fortaleza, using WiMAX technology to support these centers with videoconferencing, internet, VoIP, IP cameras, and other services. Each center will have adequate physical spaces to house a multimedia library, a computer lab, and a multipurpose room, allowing for the development of sociocultural activities and the acquisition of information in the community. These centers will function as infrastructure for evening courses in information technology for the communities, bringing social benefits and qualification to underprivileged people living in the vicinity of the CIDFs. DOI: https://doi.org/10.56238/edimpacto2025.090-079